# G(x)=x^2-7x+1 A. g(3) B.g(0)?

### Answer this question

• G(x)=x^2-7x+1 A. g(3) B.g(0)?

Answer: a)f(g(x)) = x^2-7x+12 b)g(f(x)) = x^2-x-3 c) f(f(-1))=2 (d) g(g(-3))= -9 ...
Positive: 66 %
... (x)=x^2-7x+3 and g(x)= x+1/x-3, ... well, we have x(x-7), so either x=0 or x=7 will make the denominator zero, so these 2 values are NOT allowed.
Positive: 63 %

### More resources

The Purplemath Forums. ... Nats wrote:f(x) = x^2 - 4x + 3 and g(x)= 2x - 1 solve f(x)=g(x) ... starting from x^2 - 6x = -4. x^2 - 6x + 4 = 0
Positive: 66 %
Solutions Chapter 1 1. |z 1 +z 2|2 +|z 1 − z 2|2 =(z 1 +z ... 0,y 0), B= ∂g ∂y (x 0,y 0), 2 ... (x)=(2/x3)e−1/x2 forx=0,and f(0) ...
Positive: 61 %
Performing these operations on functions is no more complicated than the notation itself. For ... (x) = 3x + 2 and g(x) ... 6x + 3(0) – 1 = 6x – 1.
Positive: 47 %
% 0 @ 0 : b 5 @ = k 5 g 5 @ b k 8 4 > a b > 8 = a b 2 0 a 8 a b 5 < k ð· a = > 2 0 = 0 = 0 < 8 : @ > ? @ > f 5 a a > @ 5 a a 0 < > 4 8 0 3 = > a b 8 ...
Positive: 24 %

Anonymous19787
Create new account

Discover Questions